Avian Navigation: Pigeon Homing as a Paradigm - Wallraff, Hans G.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2005)
How migratory birds can navigate home from their wintering grounds to their breeding sites over hundreds and thousands of kilometres has been an admired mystery over more than a century. Profound advances towards a solution of this problem have been achieved with a model bird, the homing pigeon. This monograph summarizes our current knowledge about pigeon homing, about the birds' application of a sun compass and a magnetic compass, of a visual topographical map within a familiar area and -- most surprisingly -- of an olfactory map using atmospheric chemosignals as indicators of position in distant unfamiliar areas.
Observation Data Used to Investigate Pigeon Homing -- Basic Features of Pigeon Homing -- Potential Input Signals Exploitable for Home-Finding -- The Role of the Sun -- The Role of the Geomagnetic Field -- The Role of the Chemical Atmosphere -- The Role of the Visual Landscape -- The Neural Bases of Pigeon Homing -- Homing in Other Birds -- Research History: Blind Alleys and an Unexpected Passage -- Overall Synthesis and Perspective.
Keywords: Behavioral sciences; Animal ecology; Behavioral Sciences; Animal Ecology